To retire or not to retire: intention towards concept of retirement village in Malaysia - Lim, Xin Jean; Siew, Imm Ng; Kamal Basha, Norazlyn (Asia Business Research Corporation, 2019)
The aging population has become a global phenomenon, posing as a major societal issue, especially in developing countries. The retirement village concept has emerged as a reliable option to suit the retirement lifestyle of the elderly. The present study aims to explore the perceptions of Malaysians' buying intentions of retirement village units in Malaysia. Utilizing a quantitative approach, a total of 261 usable questionnaires were collected via self-administrated method and subsequently analyzed using PLS-SEM. Perceived risk, communicability, retirement planning, and social sustainability were found significant in influencing retirement village buying intention. The research findings have implications for both developers and academicians when embarking on retirement village project developments in Malaysia.